Case Report: Multiple Nodular Thyroid - Riondi, Muhamad Afif; Santosa, Arif (Jurnal Health Sains, 2026)
Thyroid nodules are uneven and lumpy enlargements of the thyroid gland, with a prevalence of approximately 8% in the adult population and occurring more frequently in women. This case report aims to describe the evaluation and management of patients with multiple nodular thyroid. A case of a 36-year-old female patient who presented with a complaint of a neck lump that had been slowly enlarging for several months—from the size of a marble to that of a ping pong ball—is reported. The lump was palpable, solid, and painless, without symptoms of hyperthyroidism or obstruction. Physical examination revealed thyroid gland enlargement with a solid consistency. Complete blood count and HBsAg laboratory results were within normal limits. The patient was diagnosed with multiple nodular thyroid and underwent total thyroidectomy. The surgery was performed successfully without complications. Multiple nodular thyroid is generally benign but requires careful evaluation to rule out the possibility of malignancy. Definitive management through total thyroidectomy provided good outcomes in this case.